Towards Efficient Large Multimodal Model Serving - Qiu, Haoran; Biswas, Anish; Zhao, Zihan; Mohan, Jayashree; Khare, Alind; Choukse, Esha; Goiri, Íñigo; Zhang, Zeyu; Shen, Haiying; Bansal, Chetan; Ramjee, Ramachandran; Fonseca, Rodrigo (2025)
Recent advances in generative AI have led to large multimodal models (LMMs) capable of simultaneously processing inputs of various modalities such as text, images, video, and audio. While these models demonstrate impressive capabilities, efficiently serving them in production environments poses significant challenges due to their complex architectures and heterogeneous resource requirements. We present the first comprehensive systems analysis of two prominent LMM architectures, decoder-only and cross attention, on six representative open-source models. We investigate their multi-stage inference pipelines and resource utilization patterns that lead to unique systems design implications. We also present an in-depth analysis of production LMMinference traces, uncovering unique workload characteristics, including variable, heavy-tailed request distributions, diverse modal combinations, and bursty traffic patterns. Our key findings reveal that different LMM inference stages exhibit highly heterogeneous performance characteristics and resource demands, while concurrent requests across modalities lead to significant performance interference. To address these challenges, we propose a decoupled serving architecture that enables independent resource allocation and adaptive scaling for each stage. We further propose optimizations such as stage colocation to maximize throughput and resource utilization while meeting the latency objectives.